Short Communication: Records of Java mouse-deer (Tragulus javanicus Gmelin, 1788) in the Cisokan forest patches, West Java, Indonesia - ERRI NOVIAR MEGANTARA; TEGUH HUSODO; DWI RUSTAM KENDARTO; ASEP ZAINAL MUTAQIN; SUSANTI WITHANINGSIH; INDRI WULANDARI; SYA SYA SHANIDA; PUPUT FEBRIANTO; RANDI HENDRAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Megantara EN, Husodo T, Kendarto DR, Mutaqin AZ, Withaningsih S, Wulandari I, Shanida SS, Febrianto P, Hendrawan R. 2024. Short Communication: Records of Java mouse-deer (Tragulus javanicus Gmelin, 1788) in the Cisokan forest patches, West Java, Indonesia. Biodiversitas 25: 2713-2719. Mammals are bioindicators in terrestrial ecosystems due to their influence on the conservation of other species and in maintaining ecosystem balance, such as the Java mouse-deer (Tragulus javanicus Gmelin, 1788), which contributes to seed disperser on the forest floor. Information on the presence of Java mouse-deer is still limited to mammalian diversity studies; therefore, little information focuses on Java mouse-deer studies, especially in the non-conservation areas and infrastructure development areas, such as the Upper Cisokan Pumped Storage (UCPS) development in the Cianjur and West Bandung Districts. This study aims to reveal the presence of Java mouse-deer in the UCPS hydropower development area, West Java. The studies were conducted in February 2017, August 2020, and September 2022. Sign survey, camera trapping, and literature review were applied to this study. Java mouse-deer was found for ten years in the UCPS area. Java mouse-deer was found both directly and indirectly (footprints and feces). Java mouse-deer were discovered in 2012, 2017, 2020, and 2022 in the UCPS area. This species was found in the secondary forest (forest patches), shrubs, mixed gardens, and plantations. This species was most abundant in shrubs and mixed gardens near paddy fields with high levels of human activity. In shrub areas, the topography tends to be cliffy with a dense canopy, making it difficult for humans to pass. Shrub cover is dominated by calliandra (Calliandra calothyrsus Meisn.), wild sugarcane (Saccharum spontaneum L.), siam weed (Eupatorium odoratum L.), and billygoat-weed (Ageratum conyzoides L.). Java mouse-deer have been encountered for ten years. Agricultural and construction activities affect the opportunities to encounter the species. Longer-term monitoring of the densities will be essential to reveal the population of Java mouse-deer and how its distribution impacted the development of hydropower plants.